Formal and informal organizational activities of people who inject drugs in New York City: Description and correlates. - Friedman, Samuel R; Pouget, Enrique R; Sandoval, Milagros; Jones, Yolanda; Mateu-Gelabert, Pedro (Journal of addictive diseases, 2015)
Little is known about group memberships of people who inject drugs (PWID). Three hundred PWID were interviewed about formal and informal group participation and risk behaviors. Many took part in groups related to problems and resources associated with injecting drugs, religion, sports or gender. Harm reduction group and support group participation was associated with less risk behavior; sports groups participation with more risk behavior. Group involvement by PWID may be important to their lives and/or affect prevention or infectious disease transmission. More research is needed about determinants and consequences of their and other drug users' group memberships.